Structure-Function Relationship of the Sterol Transporter ABCG5/G8: Expression, Purification and Enzymatic Characterization of ABCG5/G8 Missense Loss of Function Mutations - Zein, Aiman (Université d'Ottawa / University of Ottawa, 2020)
The heterodimeric ATP-binding cassette (ABC) transporter, ABCG5/G8, is responsible for direct secretion of cholesterol and dietary sterols into the gut lumen and the bile. Inactivating mutations of ABCG5/G8 cause sitosterolemia, a rare autosomal recessive disease characterized by the accumulation of plant sterols in plasma, hypercholesterolemia and development of premature coronary heart disease. Functional and structural characterization of ABCG5/G8 is necessary to understand its mechanism and how the genetic defects impact its function. In this thesis, I expressed seventeen constructs of various disease-causing or catalytically deficient missense mutations in Pichia pastoris yeast. This establishes reagents for in vitro functional and structural studies. Secondly, I focused on two disease mutants (ABCG5-E146Q and ABCG8-R543S) and a sterol binding mutation (ABCG5-A540F) and established large-scale purification of these mutants. Using a cholesterol hemisuccinate (CHS)-dependent ATPase assay, I determined ATP hydrolysis by these three mutants and analyze their kinetic parameters. All missense mutants showed a significantly impaired ATPase activity, but the ability of ATP binding appeared unchanged between the WT and the mutants. This work demonstrates an intimate structure-function relationship in ABCG5/G8 and sheds some light on the mechanistic details of this important cholesterol-regulating ABC transporter.
Keywords: ABCG5; ABCG8; ATP-binding cassette; Cholesterol; Plant sterol; Sterol transporter; Sitosterolemia; Cardiovascular disease